1998
DOI: 10.1099/0022-1317-79-4-719
|View full text |Cite
|
Sign up to set email alerts
|

Induction of protective immunity in chickens vaccinated with infectious bronchitis virus S1 glycoprotein expressed by a recombinant baculovirus.

Abstract: A recombinant baculovirus containing the S1 glycoprotein gene of the virulent nephropathogenic KM91 strain of infectious bronchitis virus (IBV) was constructed in order to investigate protective immunity in vaccinated chickens. Results from the protection test were evaluated by re-isolation of virus from the kidneys and tracheas of vaccinated chickens after challenge with strain KM91. After three immunizations, the recombinant S1 (rS1) glycoprotein induced 50 % protection of the kidney, whilst inactivated KM91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
69
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 23 publications
4
69
0
Order By: Relevance
“…Other studies, using purified, inactivated IBV, have been successful in getting a degree of protection against respiratory tract protection, though usually at a rate of < 59% [12,51,93]; reviewed in more detail by [20]. Rather better protection with inactivated IBV has been achieved against losses in egg production [69].…”
Section: Inactivated Virus and Subunit Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies, using purified, inactivated IBV, have been successful in getting a degree of protection against respiratory tract protection, though usually at a rate of < 59% [12,51,93]; reviewed in more detail by [20]. Rather better protection with inactivated IBV has been achieved against losses in egg production [69].…”
Section: Inactivated Virus and Subunit Vaccinesmentioning
confidence: 99%
“…Induction of immunity by the S1 spike subunit has been studied with S1 prepared from purified virus [12,51] and expression using baculovirus [93]. Although protective immune responses were induced, multiple inoculations of subviral material were required and the percentage of protected chickens was too low (< 50%) for commercial application.…”
Section: Inactivated Virus and Subunit Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The S1 and S2 domain of SARS-CoV S protein can be identified by sequence alignment with other coronavirus S proteins, especially with the more conserved S2 domain (8-10). The S protein is also the major antigenic determinant for coronaviruses (9,(11)(12)(13)(14). It has recently been demonstrated that the binding of the S1 domain to its receptor angiotensinconverting enzyme 2 (ACE2) on host cells is responsible for SARS-CoV entry into cells (15).…”
mentioning
confidence: 99%
“…Therefore, the BES is currently used widely for protein expression and vaccine production. There were a few studies on the expressing IBV structure proteins by BES [18,[30][31][32][33], but no previous study has focused on developing of subunit vaccine from baculovirus co-expressing S1 and N proteins of IBV and evaluating the immune response of this type of subunit vaccine. Hence, it is necessary to co-express the S1 and N proteins by BES and develop the subunit vaccine including these two proteins.…”
Section: Introductionmentioning
confidence: 99%